Information and communications technologies in the archives and museums activities - Bilushchak, Tetiana; Fedushko, Solomia (Видавництво Львівської політехніки, 2016)
The article is devoted to the topical issue of the using of information and communications technologies in archival and museum activities. The article analyzes the international experience of using web and multimedia technologies to create a museum environment and the digital archive. It considers the current state of implementation of modern information and communications technologies in archival and museum activities in Ukraine.
Keywords: archival activity; museum activity; informatization of society; multimedia technology; web technology; virtual reality; exhibition activity